The distinctive nature of sport marketing - Chadwick, Simon (Henry Stewart Talks, 2008)
The scale and nature of sport, The need and definition of sport marketing, The direct and indirect sport marketing domains, The scope of sport marketing, The challenges facing sport marketers, Arguments for and against sport marketing